School of Biomedical Sciences, Faculty of Science, University of Queensland, Australia - Cheesman, M.J. (Pharmacognosy Communications)
The School of Biomedical Sciences (SBMS)1 at The University of Queensland (UQ) is an acknowledged leader in biomedical sciences in Australia. UQ is typically ranked around 30 globally in the top 100 for Life Sciences according to The Times Higher Education World University Rankings2 . SBMS is creating world-class biomedical scientists through excellence in research and teaching. This is achieved by attracting and nurturing the best students, the finest educators, dedicated support staff, and internationallycompetitive researchers.